1998
DOI: 10.1038/bjc.1998.512
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the anti-tumour effects of the antivascular agent 5,6-dimethylxanthenone-4-acetic acid (DMXAA) by combination with 5-hydroxytryptamine and bioreductive drugs

Abstract: SummaryThe tumour blood flow inhibitor 5,6-dimethylxanthenone-4-acetic acid (DMXAA) causes dramatic haemorrhagic necrosis in murine tumours, but activity is seen only at doses close to the toxic limit. This study investigates two approaches for increasing the therapeutic ratio of DMXAA. The first approach combines DMXAA with a second tumour blood flow inhibitor, 5-hydroxytryptamine (5-HT). Co-administration of 5-HT (700,mol kg-1) to C3H mice caused marked enhancement of DMXAA effects against MDAH-MCa-4 tumours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
73
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 37 publications
3
73
0
Order By: Relevance
“…In this study, as in the parallel phase I study of DMXAA (Jameson et al, submitted), only a single unconfirmed tumour response was seen. Synergistic activity of DMXAA in combination with bioreductive cytotoxic drugs (Cliffe et al, 1994;Lash et al, 1998), chemotherapy (notably taxanes) (Pruijn et al, 1997;Horsman et al, 1999;Wilson and Baguley, 2000), thalidomide (Cao et al, 1999), immunotherapy (Kanwar et al, 2001), radiotherapy , and radioimmunotherapy (Pedley et al, 1999) has been demonstrated in animal models, and the potential of DMXAA in cancer treatment with its novel mechanism of action is likely to lie in combination therapy with other treatment modalities.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, as in the parallel phase I study of DMXAA (Jameson et al, submitted), only a single unconfirmed tumour response was seen. Synergistic activity of DMXAA in combination with bioreductive cytotoxic drugs (Cliffe et al, 1994;Lash et al, 1998), chemotherapy (notably taxanes) (Pruijn et al, 1997;Horsman et al, 1999;Wilson and Baguley, 2000), thalidomide (Cao et al, 1999), immunotherapy (Kanwar et al, 2001), radiotherapy , and radioimmunotherapy (Pedley et al, 1999) has been demonstrated in animal models, and the potential of DMXAA in cancer treatment with its novel mechanism of action is likely to lie in combination therapy with other treatment modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of tumour vascular endothelial cells by apoptosis would be expected to increase the permeability of the vascular endothelium, providing a potential mechanism for reduction in tumour blood flow (Baguley, 2001) as demonstrated in both murine models (Zwi et al, 1994a,b;Lash et al, 1998) and in clinical studies (Rustin et al, 1998). The results also provide a possible mechanism for the DMXAA-induced extravasation of erythrocytes in murine tumours (Zwi et al, 1994b).…”
Section: Discussionmentioning
confidence: 99%
“…In preclinical studies, DMXAA was particularly effective against transplantable murine tumours with an established vasculature (Rewcastle et al, 1991), where it caused cessation of tumour blood flow, vascular collapse and tumour necrosis (Zwi et al, 1994a;Lash et al, 1998). DMXAA increased tumour necrosis factor (TNF) concentrations in plasma of both tumour bearing and non-tumour bearing mice (Philpott et al, 1995).…”
mentioning
confidence: 99%
“…Like FAA, DMXAA causes protracted inhibition of blood flow in murine tumours (Zwi et al, 1994;Lash et al, 1998) and induces extensive tumour haemorrhagic necrosis that is similar to that induced by TNF (Rewcastle et al, 1991). In situ hybridisation studies indicate that both host and tumour cells within murine colon 38 tumours express TNF mRNA after DMXAA treatment ).…”
mentioning
confidence: 99%
“…A significant decrease in tumour blood flow is observed within 1 h of administration of DMXAA, before detectable induction of cytokines (Zwi et al, 1994;Lash et al, 1998). Induced endothelial cell apoptosis in tumour tissue occurs as early as 15 min after DMXAA administration .…”
mentioning
confidence: 99%